Alternative sources of energy in Ukraine - Kriestov, V. G. (ТДАТУ, 2020)
Nowadays alternative energy has become an important part of the modern world. Due to the reduction of traditional energy sources, rising prices for them, concern about environmental issues, Ukraine as the world economy is increasingly paying attention to the search and development of nontraditional and renewable sources.
Keywords: the use of solar energy; thermoelectric converters; Seebeck effect